Cadmium Tissue Concentrations in Kidney, Liver and Muscle in Moose (Alces alces) From First Nations Communities in Northern Alberta - McAuley, Claire; Dersch, Ave; Mouille-Malbeuf, Stacey; Koppe, Bart; Sowan, Darryel (Frontiers in Sustainable Food Systems, 2018)
The consumption of traditional foods, including moose, is vitally important to Canada’s indigenous communities for dietary, social, and cultural reasons. Cadmium is a key contaminant of concern in moose as it accumulates primarily the organs, with the kidney accumulating more than the liver. The objectives of this study were to identify relationships between cadmium concentrations in the kidney, liver and muscle tissue of moose, and to estimate benchmark consumption quantities that are associated with minimal health risk for three First Nation communities: the Chipewyan Prairie Déné First Nation, the Swan River First Nation and Cold Lake First Nations. Moose quality studies were conducted with the Chipewyan Prairie Déné First Nation in 2012, the Swan River First Nation in 2014 and the Cold Lake First Nations in 2016, all located in Alberta, Canada. The measured cadmium tissue concentrations from these studies were found to be comparable to those reported in the 2016 Alberta First Nations Food, Nutrition and Environment Study and other North American studies. The results of our study suggest that linear relationships exist between cadmium concentrations in kidney and liver tissue, which can be used as a tool to predict organ concentrations in moose from northern Alberta. First Nations communities can use this information to predict cadmium tissue concentrations in both kidney and liver in the absence of actual, measured cadmium concentrations. Benchmark consumption quantities that are associated with minimal risk were estimated for the different tissue types.